ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN TEKNOLOGI MOBILE PAYMENT PADA GENERASI BABY BOOMERS DI INDONESIA - Meydy Fauziridwan; Yordan Hermawan Apidana (LP3M Universitas Putra Bangsa, 2022)
The use of technology today is enjoyed by all generations, but the baby boomers generation is the one who can have minimal knowledge of technology. The baby boomer generation itself is people who were born in 1946 – 1964. The purpose of this study is to determine the factors that influence mobile payment technology in the baby boomer generation. This research is a quantitative research and the respondents in this study were 160 respondents. In this study, samples were taken by non-probability sampling, namely by purposive sampling technique. Based on the data analysis, it is known: (1) perceived usefulness has a positive and significant effect on behavioral intention to use, (2) perceived ease of use has a positive and significant effect on behavioral intention to use, (3) perceived risk has a negative and significant effect on behavioral intention to use (4) social influence has a positive and significant effect on behavioral intention to use.